The Effect of Flip Sheet Media on Knowledge of Dysmenorrhea, Calcium Intake, Eating Pattern, and Nutritional Status of Female Adolescents - Lidia Dwi Lestari; Didik Hariyadi; Dahliansyah Dahliansyah (Borneo Scientific Publishing, 2023)
Adolescents experience rapid growth, and dysmenorrhea can interfere with activities and concentration in studying. The WHO recorded in 2017 that 90% of female adolescents experience dysmenorrhea, with 10–16% experiencing severe dysmenorrhea. The incidence rate in Indonesia is also relatively high. One of the effective nutrition education media to address dysmenorrhea related to eating patterns is the flip sheet, as it can convey information visually and gradually. This study aims to analyze the effect of flip sheet media on the knowledge of dysmenorrhea, calcium intake, eating pattern, and nutritional status of female adolescents in Limbung Village, Sungai Raya Subdistrict. This study is a pre-experimental research with a pre-and-posttest group design. The research subjects are female adolescents from Limbung Village, Sungai Raya Subdistrict. A sample of 35 respondents was taken using purposive sampling. Based on the research results, there was no significant increase in the variables of knowledge, eating patterns, and nutritional status before and after receiving nutrition education, with a p-value >0.05, but there was a significant increase in the calcium intake variable before and after receiving nutrition education, with a p-value <0.05. There is an effect of flip sheet media on the knowledge of dysmenorrhea, calcium intake, eating pattern, and nutritional status.